Flash flood counter: smart eco drain cover / Muhammad Amirul Faiz Nordin and Hasni Suryani Mat Hasan - Nordin, Muhammad Amirul Faiz; Mat Hasan, Hasni Suryani (2023)
In Malaysia, flash floods are familiar issue and always occur especially in residential areas, this can be related to the drain cover system that contributes to the occurrence of flash floods because most drains are blocked and filled with garbage and effect the drainage system become improper. The flood that hit this nation in the late 2021 and early 2022 had caused damage to living quarter, vehicles, business premises, manufacturing and agriculture sector as well as public assets and infrastructure. There are many flash floods incidents which happen due to the poor maintenance of the drainage system which is filled with garbage which obstructs the rainwater from flowing away quickly and easily. Silt, garbage and other obstructions are reducing the carrying capacity of the drainage system by up to 50 percent and thus causing flash floods. Besides, theft of metal drain cover also contribute to the flash flood issue. This is related to irresponsible of people’s attitude, corresponding to the high price of iron. Drain covers made of iron are one of the things that are potential to be stolen, this caused drains that should be covered become open drain then it causes garbage to easily enter and fill the space in the drain and finally close the water channel resulting in clogged drains and causing the occurrence of flood. Thus, the aim of this study is to develop smart eco drain cover, to assemble their prototype, to demonstrates the performance and also to market the product using. This research are using innovation framework as a methodology of the research.